The newly credentialed veterinary technician: perceptions, realities, and career challenges - Reinhard, Addie R.; Celt, Victoria P.; Pilewki, Leah E.; Hendricks, Mariel K. (Frontiers in Veterinary Science, 2025)
Previous research has shown that when comparing psychological wellbeing between credentialed veterinary technicians and human registered nurses, high levels of burnout and distress were noted within the veterinary technician population. This qualitative focus group study sought to gain a better understanding of the early-career veterinary technician experience to understand what factors might contribute to stress and burnout. Four ninety-minute qualitative focus groups were conducted with a range of two to five participants. Semi-structured interviewing was used, and focus groups were recorded, transcribed, and then analyzed. Two major categories were identified: (1) The Credentialing Journey, and (2) Challenges with the Career. Seven themes were identified in these two categories, including Credentialing: Perceptions and Reality, the Newly Credentialed Veterinary Technician, Us vs. Us, Ethical Dilemmas, Work Environment, Utilization, and Career Longevity. The findings of this study can inform future intervention research to improve the mental health and wellbeing of veterinary technicians. A focus on teaching team-based medicine, leadership skills, and conflict management in both veterinary and veterinary technician schools may help reduce team conflict. In addition, effectively utilizing veterinary technicians and increasing awareness of their value may help improve veterinary technician career satisfaction.